2014
DOI: 10.3892/mmr.2014.2565
|View full text |Cite
|
Sign up to set email alerts
|

Phenethyl isothiocyanate suppresses cervical carcinoma metastasis potential and its molecular mechanism

Abstract: Tumor metastasis is a prominent cause of treatment failure in cervical carcinoma. Phenethyl isothiocyanate (PEITC) is an active component extracted from cruciferous plants that has exhibited anticancer activity in various types of human cancer; however, its effect on the inhibition of metastasis remains unclear. The current study aimed to explore the effect of PEITC on the suppression of metastasis in HeLa cervical carcinoma cells. Multiple variables were assessed with different methods as follows: Cell viabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…It activates downstream target genes, including IL-6, IL-8, cyclin D and Bcl-2. A previous study suggests that the downstream target genes may play an important role in cervical cancer cell metastasis (28). Our results provide evidence that ATAD2 is not only important in cervical cancer cell proliferation, but is also involved in cervical cancer cell invasion and migration.…”
Section: Discussionsupporting
confidence: 71%
“…It activates downstream target genes, including IL-6, IL-8, cyclin D and Bcl-2. A previous study suggests that the downstream target genes may play an important role in cervical cancer cell metastasis (28). Our results provide evidence that ATAD2 is not only important in cervical cancer cell proliferation, but is also involved in cervical cancer cell invasion and migration.…”
Section: Discussionsupporting
confidence: 71%
“…Our previous study showed that PEITC and BITC suppress metastasis potential of lung cancer cells . Interestingly, other groups also revealed the inhibitory effect of isothiocyanates on metastasis in ovarian cancer, prostate cancer, breast cancer, and cervical carcinoma . Although these studies indicated that several mechanisms are involved, such as the inhibition of CRM1‐mediated nuclear export and mTOR‐STAT3 pathway, regulation on miRNA‐194, and involvement of HIF‐1alpha, however, the role of autophagy has not been elucidated.…”
Section: Discussionmentioning
confidence: 98%
“…It was considered to act via the transforming growth factor (TGF)β/Smad2 pathway, evident by increasing TGFβ, IL6, and IL8 production and Smad2 phosphorylation. 116 In another study, phenethyl isothiocyanate was demonstrated to have cytotoxic potential against OVCAR-3 cells by its anti-proliferative effect in a dosedependent manner. Apoptosis induction was through caspase-3 and -9 activation.…”
Section: 73mentioning
confidence: 98%